Strategi Pemasaran Yang Tepat Guna Dalam Menghadapi Persaingan Pasar UMKM - Basalamah, Muhammad Ridwan; Athia, Ita; Jannah, Miftakhul (JU-ke: Jurnal Ketahanan Pangan, 2018)
Small and Medium Enterprises (SMEs) have a big role in national economic development. In addition to playing a role in national economic growth and employment, SMEs also play a role in the distribution of development results and are the driving force for the growth of national economic activity. This study aims to 1) To find out internal factors which include strengths and weaknesses; 2) To find out external factors that include opportunities and threats; 3) To find out what strategies can be produced by using SWOT analysis, in the face of market competition. This research use desciptive qualitative approach. Location of research on the Ganesha stick home industry in Trawas sub-district, Mojokerto district, East Java Province. The results showed that the internal marketing analysis of the environment, vegetable processing businesses and tubers of the Ganesha stick industry had major strengths in product variations, while the main weaknesses were high product selling prices and an external marketing environment analysis that had the main opportunity to increase customer demand. and the main threat is increased production costs. Based on the results of the interviews, it was obtained the priority marketing strategies for vegetable processing businesses and the Ganesha home industry tubers, namely improving the appearance of the product through improved packaging.